Combined effects of structure and partial saturation in natural soils - Pereira, Jean-Michel (2014)
The mechanical behaviour of natural clays is significantly affected by their in situ or initial structure in the form of cementation or interparticle bonding. This behaviour can differ substantially from the behaviour of reconstituted clays. Suction as well as plastic volumetric strains drive isotropic hardening/softening as this is a simple way to account for the phenomenon of volumetric collapse upon wetting and the stiffening effect that suction has on the soil skeletal response. A model that combines unsaturated and structured behavior is presented and then used to simulate stress strain behaviour observed for an unsaturated natural clay subjected to isotropic load paths. A parametric analysis is performed to observe the influence suction hardening has on mobilized strengths. It is also shown that the model can predict the maximum of collapse of unsaturated soils.